1997
DOI: 10.1080/01688639708403853
|View full text |Cite
|
Sign up to set email alerts
|

California verbal learning test: Normative data for the elderly

Abstract: Overlapping age tables were developed, separately for males and females, to provide additional normative information for the California Verbal Learning Test (CVLT) and extend the normative data to persons older than 80 years of age. Participants were 92 males and 120 females with means for age and education of 70.58 years (SD = 6.98) and 14.92 years (SD = 2.56), respectively. Normative information was also provided for additional measures of retention rate and proportion of perseverations and intrusions. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 15 publications
5
65
0
Order By: Relevance
“…There is a known association between increasing age and decreasing performance (Delis et al., 2000; Wiens, Tindall, & Crossen, 1994; Paolo, Troster, & Ryan, 1997) and hence the CVLT‐II manual recommends controlling for age when analyzing CVLT‐II performance (Delis et al., 2000). In our sample, age was a statistically significant independent predictor of poorer verbal memory performance across all CVLT‐II subscales, which may be due to a combination of normal cerebral aging processes leading to slower verbal memory processing—a finding consistent with prior reports in mTBI (Jacobs et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a known association between increasing age and decreasing performance (Delis et al., 2000; Wiens, Tindall, & Crossen, 1994; Paolo, Troster, & Ryan, 1997) and hence the CVLT‐II manual recommends controlling for age when analyzing CVLT‐II performance (Delis et al., 2000). In our sample, age was a statistically significant independent predictor of poorer verbal memory performance across all CVLT‐II subscales, which may be due to a combination of normal cerebral aging processes leading to slower verbal memory processing—a finding consistent with prior reports in mTBI (Jacobs et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports regarding education effects on the CVLT‐II are more unclear; Paolo et al. (1997) report that education affects only 14% of CVLT‐II indices, and Wiens et al. (1994) did not find a consistent contribution of education to CVLT‐II.…”
Section: Discussionmentioning
confidence: 99%
“…The CVLT-II has high internal consistency (α= .94; Delis et al, 2000) and demonstrated validity of responses in adults across age and sex (Paolo, Troster, & Ryan, 1997).…”
Section: Episodic Memorymentioning
confidence: 99%
“…On the long-delay free recall variable, the e4-group recalled slightly more words compared to the e4+ group (10.1 vs. 8.1). The raw scores were also converted to standard scores with age and gender corrected norms (Paolo et al, 1997). Again, both e4+ and e4-groups performed within normal limits (e4+ z-score = -.25; e4-z-score = .21) compared to same age peers.…”
Section: Contrast Measuresmentioning
confidence: 99%
“…In separate comparisons, raw scores from DS and SS were converted to age-scaled percentile scores and groups were compared with 2-tailed t-tests. In addition, groups were compared on the total number of words recalled on the CVLT long-delay free recall (LDFR), and on age and gender adjusted standard scores (Paolo, Troester, & Ryan, 1997) for LDFR.…”
Section: Statistical Analysesmentioning
confidence: 99%